2010
DOI: 10.1007/s10800-009-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of hydrogen nanobubbles in alkaline electrolyzed water and its rinse effect for sulfate ion remained on nickel-plated surface

Abstract: More than ordinary rinsing using pure water, cathode water obtained by electrolysis of dilute potassium carbonate aqueous solution (alkaline electrolyzed water: AEW) exhibits a stronger rinse effect for elimination of remaining sulfate ions when rinsing nickel-plated surfaces. This rinse effect was recognized even for AEW that was used 24 h after it was produced, but not 1 week after. Behaviors of hydrogen nanobubbles observed by dynamic light scattering revealed nanobubbles of about 128-nm diameter even 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We have not directly demonstrated that the nanoparticles produced by electrolysis are gaseous, but the balance of the evidence is that they are indeed nanobubbles. Consistent with previous reports of nanoparticle production from solutions supersaturated by electrolysis, we will henceforth refer to them as nanobubbles. The size and concentration of nanobubbles produced by electrolysis were determined using the Nanosight instrument. Samples of ec-H 2 O NaCl were filtered through a 450 nm filter before introduction into the NanoSight cell.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have not directly demonstrated that the nanoparticles produced by electrolysis are gaseous, but the balance of the evidence is that they are indeed nanobubbles. Consistent with previous reports of nanoparticle production from solutions supersaturated by electrolysis, we will henceforth refer to them as nanobubbles. The size and concentration of nanobubbles produced by electrolysis were determined using the Nanosight instrument. Samples of ec-H 2 O NaCl were filtered through a 450 nm filter before introduction into the NanoSight cell.…”
Section: Resultsmentioning
confidence: 95%
“…Electrolysis has also been reported to produce nanobubbles in the bulk. Electrolysis results in the supersaturation of oxygen and hydrogen in the anodic and cathodic streams of the solution, respectively, causing bubbles to be nucleated. Larger bubbles quickly rise to the surface and burst, but particle sizing techniques show persistent nanoparticles of around 100 nm following electrolysis that are not present in control solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The creaming process is significantly slower for small nanoscale bubbles; thus, a higher level of stability of aqueous nanobubble suspensions can be expected. Utilization of gas nanobubbles is considered to be beneficial in a variety of applications, including agriculture, aquaculture, industrial manufacturing, energy saving and diesel engine performance, , cleaning, , and growth of lives . In the past, it was believed that gas nanobubbles cannot exist in water due to the high pressure generated by the gas–water surface tension, which is inversely proportional to the radius of the bubble (Young–Laplace equation).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating gas bubbles in the water used for cleaning has been reported for diverse substrates such as silicon wafers, mica, nickel-plated surfaces, highly oriented pyrolytic graphite (HOPG), gold surfaces, stainless steel coupons and polypropylene pipe. 39,43,98,105,[121][122][123][124][125] Burfoot et al first showed that adding bubbles into cleaning water during ultrasonic cleaning improves the removal of biofilm, carbohydrate, fat and protein deposits from steel surfaces. They suggested that the cleaning is due to the action of the bubbles rather than the cavitation events associated with ultrasonic cleaning.…”
Section: Cleaningmentioning
confidence: 99%
“…They showed that AEW cleans and removes sulfate ions efficiently from the nickel-plated surface due to the ion exchange reaction between hydroxide ions located at the nanobubble interface and the sulfate ions remained on the nickel surface. 43 A recent study by Zhu et al investigated the cleaning efficacy of bulk nanobubbles in the removal of model contaminants bovine serum albumin and lysozyme from silicon wafers with opposite wettability (hydrophilic and hydrophobic). They found that bulk nanobubbles can prevent the fouling of both surfaces and remove the contamination from hydrophilic surfaces but not from hydrophobic surfaces.…”
Section: Cleaningmentioning
confidence: 99%